Предмет: Алгебра,
автор: viktoria83446
Помогите пожалуйста
Приложения:
Ответы
Автор ответа:
1
Відповідь: mn/( n - m ) .
Пояснення:
m + ( m² + mn )/( n - m ) * m/( m + n ) =
1) ( m² + mn )/( n - m ) * m/( m + n ) = m( m + n )/( n - m ) * m/( m + n ) =
= m²/( n - m ) ;
2) m + m²/( n - m ) = [ m( n - m ) + m² ]/( n - m ) = ( mn - m² + m²)/( n - m ) =
= mn/( n - m ) .
Похожие вопросы
Предмет: Қазақ тiлi,
автор: nazgul030194
Предмет: Геометрия,
автор: danila140410
Предмет: Физика,
автор: evakrupina8888
Предмет: Українська мова,
автор: mendenkoolik
Предмет: Алгебра,
автор: fgvvhhbghbg